Homoseksualiteit: Die standpunte van die Nederduitse Gereformeerde Kerk en die Nederduitsch Hervormde Kerk van Afrika in 2007 - Strauss, Piet J. (HTS teologiese studies, 2011)
Homosexuality: The viewpoints of the Dutch Reformed Church (DRC) and the Netherdutch Reformed Church of Africa (NRCA) in 2007 These two churches, through their broadest assembly namely the General Synod and the General Church Assembly respectively, show remarkable similarities in their approach to Scripture on the matter of homosexuality, the position of gay people in church life and the time frame in which they took decisions on these matters. The point of departure for both is marriage as something only for one husband and one wife. This is explicitly complemented by the NRCA with a limitation of sexual intercourse to marriage, which rules out the possibility of homosexuality. In the DRC the same principle is tradition, thus basicly coming to the same conclusion as the NCRA. The reason for these similarities is not that the two assemblies openly copied each other, but the fact that they both are reformed churches in Southern Africa serving, mainly, Afrikaners. Perhaps these similarities supply another reason for the present increase in cooperation between the two churches.